Psychological Features Of Forming Professional Skills In Future Teachers (Journal of Pedagogical Inventions and Practices, 2025)
This article highlights the psychological features of the formation of professional skills in future teachers, analyzes the processes of formation of professional skills, abilities, self-awareness of the individual, and professional growth. The importance of the educational environment, psychological diagnostics, and training in the formation of professional skills is also described. Based on the research results, recommendations aimed at improving the professional training of future teachers have been developed.